Prognosis of large vessel involvement in large vessel vasculitis. Issue 108 (March 2020) - Vautier, Mathieu; Dupont, Axelle; de Boysson, Hubert; Comarmond, Chloé; Mirault, Tristan; Mekinian, Arsène; Lambert, Marc; Ferfar, Yasmina; Aouba, Achille; Cacoub, Patrice; Resche-Rigon, Matthieu; Saadoun, David
Abstract: Objectives: To assess prognosis factors and outcome of large vessel involvement (LVI) in large vessels vasculitis (LVV) patients. Methods: Retrospective multicenter study of characteristics and outcomes of 417 patients with LVI including 299 Takayasu arteritis (TAK) and 118 Giant cell arteritis (GCA-LVI) were analyzed. Logistic regression analysis assessed prognosis factors in LVV patients. Outcome of LVI among TAK and GCA-LVI patients (ischemic complications, aneurysms complications, relapses and revascularization) were assessed. Results: In multivariable analysis, stroke/transient ischemic attack [HR: 3.63 (1.46–9.04), p  = 0.006] was independently associated with vascular complications in LVV. The 10-years aneurysm free survival was significantly lower [67% (48–93) vs 89% (84–95), p  = 0.02] in GCA-LVI compare to TAK patients. The 5-years relapse free survival was significantly lower [47% (37–60) vs 69% (63–75), p  < 0.001, ] in GCA-LVI compare to TAK patients. The 10-years revascularization free survival was significantly lower [55% (48–64) vs 76% (59–99), p  < 0.001] in TAK compare to GCA-LVI patients. After a median follow-up of 5 years, 16 (5.4%) TAK and 7 (5.9%) GCA-LVI patients died, mainly of aneurysm (26%) and ischemic complications (26%). Conclusion: This large nationwide cohort of LVI provided prognosis factors of vascular complications in LVV patients. TAK and GCA-LVI have different long-term outcome in term of aneurysm development, relapse and revascularization. Highlights: Stroke increase by 4 times the odd of vascular complications and/or death in large vessel vasculitis. GCA-LVI develop more aneurysm and have higher relapse rate than patients with TAK. TAK patients have more large vessel stenosis and revascularization than GCA-LVI patients.